Strengthening Malawian youth resilience by transforming over 500 lives using a business incubation approach - Slane, David; Mzumara, Grace; Nkhambule, Emily; Kadammanja, Ramadhan; Chingakule, Oganive (2025)
The Business Acceleration for Youth project has achieved diverse outcomes, including supporting 500 youth-led businesses, generating 395 additional jobs, increasing household income and assets, and boosting total annual revenues to more than US$216,000. Young entrepreneurs have diversified ventures, formed business partnerships, and leveraged US$64,371 in additional investment, contributing to their resilience and sustainability. The project also strengthened the capacity of its six main implementing partners in monitoring and evaluation, training service delivery, and sub-grantee monitoring, fostering a robust business incubation ecosystem.